P-LEACH: An Efficient Cluster-Based Technique to Track Mobile Sinks in Wireless Sensor Networks. (16th September 2014) - Cho, Sungchol; Han, Li; Joo, Bokgyu; Han, Sunyoung
Abstract : For a wireless sensor network (WSN) with a large number of inexpensive sensor nodes, energy efficiency is the major concern in designing network structure and related algorithms. If network collects sensor data using mobile sinks, object tracking mechanism must consider the energy efficiency of sensor nodes in the networks as a whole. Recently research works on WSNs with mobile sinks apply prediction techniques for sink tracking in order to improve tracking precision while keeping the number of active nodes to the minimum. In this paper, we analyze existing works for sink tracking in WSN and propose P-LEACH that is cluster-based prediction technique for WSN with mobile sinks. Simulation results show that P-LEACH performs better than previous techniques in terms of energy saving of sensor nodes and data transmission performance.